Dinamika Kebijakan Pariwisata Terhadap Perkembangan Ekonomi Masyarakat Di Kabupaten Sorong - Vijay Rasyid Badarudin; Vijayanti, Yusmita; Refra, Mohamad Saleh; La Basri (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2024)
This research examines the dynamics of tourism policy and its impact on the economic development of society in Sorong Regency, Southwest Papua. This research uses qualitative methods with descriptive analysis to describe the impact of the policy.  Data collection techniques include observation, interviews and literature review. The research results show that tourism policy in Sorong Regency has had a positive and significant impact on the community's economy. There is an increase in the number of tourists visiting, which contributes to the growth of local community income through increased employment and business opportunities in the tourism sector. However, there are still challenges such as economic dependence on tourism and the need to increase human resource capacity and adequate supporting infrastructure. Apart from that, the economic development of the community in Sorong Regency is greatly influenced by holistic and sustainable tourism policies, as well as synergy between the government, community and tourism industry players. Policy recommendations include strengthening tourism promotion, improving the quality of services and infrastructure, and diversifying the economy to reduce dependence on the tourism sector.